Implementation of competency-based medical education: are we addressing the concerns and challenges? - Hawkins, Richard E; Welcher, Catherine M; Holmboe, Eric S; Kirk, Lynne M; Norcini, John J; Simons, Kenneth B; Skochelak, Susan E (Medical education, 2015)
Context Competency‐based medical education (CBME) has emerged as a core strategy to educate and assess the next generation of physicians. Advantages of CBME include: a focus on outcomes and learner achievement; requirements for multifaceted assessment that embraces formative and summative approaches; support of a flexible, time‐independent trajectory through the curriculum; and increased accountability to stakeholders with a shared set of expectations and a common language for education, assessment and regulation. Objectives Despite the advantages of CBME, numerous concerns and challenges to the implementation of CBME frameworks have been described, including: increased administrative requirements; the need for faculty development; the lack of models for flexible curricula, and inconsistencies in terms and definitions. Additionally, there are concerns about reductionist approaches to assessment in CBME, lack of good assessments for some competencies, and whether CBME frameworks include domains of current importance. This study will outline these issues and discuss the responses of the medical education community. Methods The concerns and challenges expressed are primarily categorised as: (i) those related to practical, administrative and logistical challenges in implementing CBME frameworks, and (ii) those with more conceptual or theoretical bases. The responses of the education community to these issues are then summarised. Conclusions The education community has begun to address the challenges involved in implementing CBME. Models and guidance exist to inform implementation strategies across the continuum of education, and focus on the more efficient use of resources and technology, and the use of milestones and entrustable professional activities‐based frameworks. Inconsistencies in CBME definitions and frameworks remain a significant obstacle. Evolution in assessment approaches from in vitro task‐based methods to in vivo integrated approaches is responsive to many of the theoretical and conceptual concerns about CBME, but much work remains to be done to bring rigour and quality to work‐based assessment. Discuss ideas arising from the article at http://www.mededuc.com discuss.